EFFICACY AND SAFETY OF RADIUM-223 AND STANDARD OF CARE IN PATIENTS WITH BREAST CANCER AND BONE METASTASIS: A SYSTEMATIC REVIEW AND META-ANALYSIS - Felipe Alves MOURATO; Lucas Yuji Gomes ITIKAWA; Débora Mendes BRAUN; Simone Cristina Soares BRANDÃO; Lauro WICHERT-ANA (Hematology, Transfusion and Cell Therapy, 2024)
Summary: Radium-223 (Ra-223) has been used to treat metastatic bone disease in prostate cancer, improving overall survival and quality of life. Breast cancer often presents bone metastasis too, but it is often associated with other sites of disease. In such cases, the addition of Ra-223 to the standard of care (SC) may be beneficial. Therefore, our objective is to determine if the use of Radium-223 plus SC is beneficial for metastatic bone breast cancer patients through a systematic review and meta-analysis. A comprehensive search was conducted across MEDLINE, EMBASE, and CENTRAL databases. The search strategy included the following terms: “Breast cancer” AND “Radium-223”. The selection criteria encompassed both single-arm and randomized controlled trials (RCT). MedCalc® Statistical Software was used. Hazard ratios (HR) were preferred. Odds ratios (OR) or Relative risk (RR) were used when HR was not disponible. For single-arm studies, a proportion meta-analysis was performed. Random-effects methods were used. The initial search yielded 349 articles, 28 articles were reviewed with full-text, and 5 were considered eligible (3 RCT and 2 single-arm studies). SC therapy included: capecitabine, paclitaxel, exemestane plus everolimus and hormonal therapy. Overall, the group submitted to Ra-223 showed a trend to have better symptomatic skeletal event-free survival – SSEFS - (HR: 0.855, CI: 0.643-1.138) and pain improvement (OR: 1.308. CI: 0.780-2.196), but without statistical significance. The pooled analysis showed no difference between arms for serious adverse effects (RR: 0.836. CI: 0.331-2.112). The proportion of SAE in patients submitted to Ra-223 plus SC was 20.1% (CI: 3.6-45.3%). Conclusão: Ra-223 plus SC in bone metastatic breast cancer patients showed a trend to better SSEFS and pain improvement. However, the low number of RCT studies and the high heterogeneity of SC are great limitations. Results from ongoing RCT (everolimus and avelumab) can change this scenario.